Pesan Profetik Lingkungan dalam Hadis - Muhammad Akmaluddin (Jurnal Penelitian, 2017)
The lack of understanding of religious texts, anthropocentric views and lack of integral human consciousness in the universe is one of the causes of environmental destruction. Understanding of environmental prophetic message in á¸¥ÄdÄ«th is one way to solve the problem. The sentences relating to maintaining the environment in the á¸¥ÄdÄ«th are á¸¥afiáº“a and ra'Ä, while those pertaining to corrupting are fasada and halaka. Using the thematic approach to the sentence in various editorials of the á¸¥ÄdÄ«th, I found the basic ideas about the prophetic message of the circulation conveyed by the Prophet Muhammad. In keeping with the environment, prophetic messages cover maintenance goals, inclusive ownership, positive contributions, use-based usage, sustainable programs, limited utilization and jointly controlled use. The environmental destruction includes exploitative goals, exclusive ownership, negative contributions, incorrect use, and unsustainable, unlimited and self-supervised programs. The religious texts on the environment in the á¸¥ÄdÄ«th are not dead texts. This text should always be turned on to bring a new interpretation of the existing environmental phenomenon.